The reproductive bargain : deciphering the enigma of Japanese capitalism - Gottfried, Heidi, 1955- (Studies in critical social sciences ;, 2015)
The Reproductive Bargain reveals the institutional sources of labor insecurities behind Japan's postwar employment system. This economic juggernaut's decline cannot be understood without reference to the reproductive bargain. Gendering institutional analysis is a key to deciphering the enigma of Japanese capitalism.